Arduino Based Power Meter Using Instantaneous Power Calculation Method - Tiong , Meng Chung; Hamdan, Daniyal (2015)
This paper describes the design and development of a single phase power meter using instantaneous power calculation method. It is an electrical device that is used in power system to measure the amount of electric power consumed by electrical appliance. It is closely related to the field of monitoring electric energy consumption which it involve both current and voltage signal from power system. In this research study, an accurate power meter is to be produced by using instantaneous power calculation method from the signal obtained from voltage and current sensors. Voltage and current signal are sampled and analysed by using Arduino Due as control unit, where the instantaneous power calculation takes place. The developed power meter is suitable to be used on single phase electrical appliances with its maximum current not exceeding 13A with operating accuracy up to 96.54%.